Acute midgut volvulus in a septuagenarian with secondary jejunoileal diverticulitis and undiagnosed congenital malrotation: an unusual presentation. Issue 11 (12th November 2020) - Sigler, Gregory; Baker, Laura; Tadros, Shaheer; Rekman, Janelle; Apte, Sameer S
Abstract: A 79-year-old male presented with abdominal pain, incidental umbilical hernia and acute midgut volvulus that was not detected until surgical exploration. When he presented to hospital, computed tomography (CT) findings indicated perforated jejunoileal diverticulitis; however, in the operating room clockwise volvulization of the jejunum and ileum, secondarily inflamed jejunoileal diverticula, incomplete malrotation (right-sided duodenojejunal flexure), right retroperitoneal adhesions (Ladd's bands) and numerous other congenital adhesive bands were found. A modified Ladd's procedure and umbilical hernia repair were completed including detorsion, division of Ladd's bands with medialization of the cecum and lysis of other congenital adhesions without appendectomy. The patient recovered to baseline function by 3 weeks postoperatively. Acute midgut volvulus is a life-threatening surgical emergency that is exceptionally rare in the elderly. CT is relatively insensitive, so misdiagnosis is common. A high index of suspicion is required, especially in patients with a history of congenital gastrointestinal abnormalities. Prompt surgical exploration for correction and prevention is crucial.